1991
DOI: 10.1007/bf02583983
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of urolithiasis in the elderly

Abstract: To estimate the epidemiology of upper urinary stones in the elderly, a total of 1,957 patients (1,349 men and 608 women) with urolithiasis were studied. The ratio of men to women was approximately 3:1 in middle-aged (between 30 and 59 years), 1:1 in young (29 or younger) and 1:1 in old patients (60 or older). Compared with the age distribution of the entire Japanese population, the incidence of urinary stones was very low in both male and female children, twice as high in middle-aged men, slightly higher in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Few studies which have investigated urine from normal subjects have not reported any significant differences in urinary constituents between the young and old population [21]. Therefore, though we did not analyze the urine from subjects without a history of stone disease in this study, the results are considered to be reliable for comparison of metabolic characteristics between young and old generations.…”
Section: Discussionmentioning
confidence: 89%
“…Few studies which have investigated urine from normal subjects have not reported any significant differences in urinary constituents between the young and old population [21]. Therefore, though we did not analyze the urine from subjects without a history of stone disease in this study, the results are considered to be reliable for comparison of metabolic characteristics between young and old generations.…”
Section: Discussionmentioning
confidence: 89%
“…The male-dominant gender differences in the urine oxalate excretion and incidence of oxalate stones have also been observed in adult but not in young and old human patients [7-9, 22, 26, 48], thus indicating that sex hormones could be an important contributor to gender-dependent incidence of this disease in adult humans [22]. However, possible differences in the expression of sat-1 in liver and kidneys, as well as the correlation with the plasma and urine oxalate in humans, to our knowledge have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Men exhibit higher oxalate excretion levels than women [26], as well as higher incidence of oxalate stones [7]; the incidence is two to threefold higher in male patients in middle age (30-59 years) but similar in both genders in young and old patients [7,8,22,48]. Furthermore, in a few studies of experimental nephrolithiasis in rats treated with ethylene glycol, testosterone stimulated, whereas female sex hormones inhibited, urine excretion of oxalate and formation of oxalate stones [15,25].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of CaOx urolithiasis in the middle aged population is 2 to 3 times higher in men than in women, whereas in the young and elderly population, this male-dominant prevalence is absent (161)(162)(163). The male-dominant urolithiasis was initially associated with greater body mass and body surface area, which are positively correlated with higher rates of urine oxalate, Ca…”
Section: Sex and Species Differences Effects Of Hormones And Heavy Mmentioning
confidence: 99%